Green Growth Strategy and Environmental Policy Integration in Sustainable Economic Development: A Review of Bibliometric Analysis - Halomoan Hutajulu; Usman Tahir; Eva Yuniarti Utami; Iwan Harsono; Titi Yuniarti (West Science Social and Humanities Studies, 2024)
This study presents a comprehensive review of literature on green growth strategy and environmental policy integration in sustainable economic development, utilizing bibliometric analysis as a methodological approach. Over four decades of scholarly contributions were examined, revealing a substantial body of literature with significant scholarly impact. Through citation metrics and network visualizations, key thematic clusters emerged, highlighting discussions on sustainable economic development, firm strategies for sustainability, green job markets, and technological innovations for environmental purposes. The analysis underscores the importance of integrating environmental considerations into economic decision-making processes and offers insights for policymakers, researchers, and practitioners to inform evidence-based decision-making and guide future research agendas. The findings contribute to advancing theoretical understanding and empirical insights into the interplay between green growth, environmental policy integration, and sustainable economic development, thereby facilitating progress towards a more equitable and environmentally resilient future.